Gain of Function Research: the Clairvoyant Lens on Pandemics - Sudhir BHANDARI; Amitabh DUBE; Bhoopendra PATEL; Amit TAK; Minal KACHHAWA; Jitendra Kumar GUPTA; Kapil GUPTA; Shivankan KAKKAR (Modern Medicine)
Pandemic influenza viruses have emerged three times in this century. It is important to examine the potential risk of novel microorganisms/viruses through the add-on research mechanism of Gain of Function Research (GoFR). This mechanism consists of the practice of serial passaging of microorganisms to increase their transmissibility, virulence, immunogenicity, and host tropism through the inclusive feature of selective pressure of culture medium. Although, the GoFR can be a double-edged sword that has the potential to give an insight and better appreciation of current and future pandemics with antecedent apprehension of initiating a pandemic, itself. Moreover, with its inherent potential to give a head start on a virus, GoFR has the potential to develop vaccines or therapeutics, before the virus emerges in its true virulent form. Likewise, the GoFR studies can be vital in research on antivirals and antimicrobial agents and can help inform the development of combination therapies. Passive immunotherapy, which often includes a combination of products, is particularly dependent on GoFR experiments for evaluating efficacy. GoFR if made use of meticulously and with caution could help Medical Sciences and Humankind tremendously.